Sensation Homeopathy: An Overview - Sankaran, Rajan (Homœopathic Links, 2012)
As in any other science new developments to further improve homeopathy are regularly presented. Sensation homeopathy as developed by Rajan Sankaran and his colleagues seems to be a development that is there to stay. This is underlined by a growing number of homeopaths that have come to master it. This article presents an overview of the method by its initiator.
Keywords: Sensation homeopathy; Vital sensation; Miasms; Kingdoms; Levels of experience; Case taking; Integration of methods